(-6,-1) , (0,-9)

Slope is equal to the change in y over the change in x, or rise over run.

m=change in ychange in x

The change in x is equal to the difference in x-coordinates (also called run), and the change in y is equal to the difference in y-coordinates (also called rise).

m=y2-y1x2-x1

Substitute in the values of x and y into the equation to find the slope.

m=-9-(-1)0-(-6)

Simplify.

Simplify the numerator.

Multiply -1 by -1.

m=-9+10-(-6)

Add -9 and 1.

m=-80-(-6)

m=-80-(-6)

Simplify the denominator.

Multiply -1 by -6.

m=-80+6

Add 0 and 6.

m=-86

m=-86

Reduce the expression by cancelling the common factors.

Cancel the common factor of -8 and 6.

Factor 2 out of -8.

m=2(-4)6

Cancel the common factors.

Factor 2 out of 6.

m=2⋅-42⋅3

Cancel the common factor.

m=2⋅-42⋅3

Rewrite the expression.

m=-43

m=-43

m=-43

Move the negative in front of the fraction.

m=-43

m=-43

m=-43

m=-43

Substitute the value of m into the slope-intercept form of the equation, y=mx+b.

y=(-43)⋅x+b

Substitute the value of x into the slope-intercept form of the equation, y=mx+b.

y=(-43)⋅(-6)+b

Substitute the value of y into the slope-intercept form of the equation, y=mx+b.

-1=(-43)⋅(-6)+b

Rewrite the equation as (-43)⋅(-6)+b=-1.

(-43)⋅(-6)+b=-1

Simplify each term.

Cancel the common factor of 3.

Move the leading negative in -43 into the numerator.

-43⋅-6+b=-1

Factor 3 out of -6.

-43⋅(3(-2))+b=-1

Cancel the common factor.

-43⋅(3⋅-2)+b=-1

Rewrite the expression.

-4⋅-2+b=-1

-4⋅-2+b=-1

Multiply -4 by -2.

8+b=-1

8+b=-1

Move all terms not containing b to the right side of the equation.

Subtract 8 from both sides of the equation.

b=-1-8

Subtract 8 from -1.

b=-9

b=-9

b=-9

The values of the slope and y-intercept are m=-43 and b=-9.

m=-43

b=-9

Find the Slope and Y-Intercept (-6,-1) , (0,-9)